2011
DOI: 10.4306/pi.2011.8.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Anger in Elderly Patients with Depressive Disorders

Abstract: ObjectiveThis study was conducted to investigate anger in elderly patients with depressive disorders.MethodsThe subjects included 216 elderly patients with depression and 198 controls. All subjects were assessed by the State and Trait Anger Inventory (STAXI), Aggression Questionnaire (AQ), Reaction Inventory (RI).ResultsElderly patients with depressive disorder showed lower levels of trait anger and anger expression on the STAXI, lower levels of verbal aggression and hostility on the AQ, and lower levels of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Öte yandan depresyon ve öfke arasında da bir ilişki vardır ve birçok çalışmada depresyon ile bilhassa bastırılmış öfkenin ilişkili olduğu ortaya konmuştur. Öfkenin bir alt tipi olan bastırılmış ya da diğer bir deyişle içe dönük öfke, depresyonun bir klinik bulgusu olabilir [30][31][32][33] . Bazı çalışmalarda ise dışa dönük öfke, depresif semptomlarla ilintili bulunmuş ve şiddet davranışlarıyla ilişkilendirilmiştir 33,34 .…”
Section: Discussionunclassified
“…Öte yandan depresyon ve öfke arasında da bir ilişki vardır ve birçok çalışmada depresyon ile bilhassa bastırılmış öfkenin ilişkili olduğu ortaya konmuştur. Öfkenin bir alt tipi olan bastırılmış ya da diğer bir deyişle içe dönük öfke, depresyonun bir klinik bulgusu olabilir [30][31][32][33] . Bazı çalışmalarda ise dışa dönük öfke, depresif semptomlarla ilintili bulunmuş ve şiddet davranışlarıyla ilişkilendirilmiştir 33,34 .…”
Section: Discussionunclassified
“…Failure DEPRESSION Research has shown that the constructs of anger and depression overlap significantly (59) so it is important to understand the extent of the relationship and overlap that anger and depression share. Baeg et al (3) found individuals who report severe depression symptoms also report higher anger experience and anger expression.…”
Section: Chapter 3: Possible Mediating Factors Between Anger and Heartmentioning
confidence: 99%
“…2 Step two includes the following predictors: (constant), days in study, gender, household income, baseline creatinine levels, base line ejection fraction, history of smoking, age, and all hostility/anger measures. 3 Due to skewness, all-cause hospitali zations were truncated at 5. Hostile I. I 0 .68-1.80 1.03 .62-1.71 Affect Note: * denotes p _: : : : .05, ** is p S O I, *** is pSOO I 'Step one includes the following predictors: (constant), months in the study, gender, household income, baseline creatinine levels, baseline ejection fraction, history of smoking, and age.…”
Section: Aim Onementioning
confidence: 99%
See 2 more Smart Citations